Circulating but not immobilized N-deglycosylated von Willebrand factor increases platelet adhesion under flow conditions - Fallah, M. A. (AIP Publishing LLC, 2013)
The role of von Willebrand factor (VWF) as a shear stress activated platelet adhesive has been related to a coiled-elongated shape conformation. The forces dominating this transition have been suggested to be controlled by the proteins polymeric architecture. However, the fact that 20% of VWF molecular weight originates from glycan moieties has so far been neglected in these calculations. In this study, we present a systematic experimental investigation on the role of N-glycosylation for VWF mediated platelet adhesion under flow. A microfluidic flow chamber with a stenotic compartment that allows one to mimic various physiological flow conditions was designed for the efficient analysis of the adhesion spectrum. Surprisingly, we found an increase in platelet adhesion with elevated shear rate, both qualitatively and quantitatively fully conserved when N-deglycosylated VWF (N-deg-VWF) instead of VWF was immobilized in the microfluidic channel. This has been demonstrated consistently over four orders of magnitude in shear rate. In contrast, when N-deg-VWF was added to the supernatant, an increase in adhesion rate by a factor of two was detected compared to the addition of wild-type VWF. It appears that once immobilized, the role of glycans is at least modified if not—as found here for the case of adhesion—negated. These findings strengthen the physical impact of the circulating polymer on shear dependent platelet adhesion events. At present, there is no theoretical explanation for an increase in platelet adhesion to VWF in the absence of its N-glycans. However, our data indicate that the effective solubility of the protein and hence its shape or conformation may be altered by the degree of glycosylation and is therefore a good candidate for modifying the forces required to uncoil this biopolymer.